Association between PER and CRY gene polymorphisms and the response to caffeine citrate treatment in infants with apnea of prematurity - Xie, Jiang-Biao; Zhuang, Wei; Zhu, Yao; Zheng, Zhi; Huang, Yan-Ru; Ma, Si-Min; Lin, Xin-Zhu (Frontiers in Pediatrics, 2024)
Background Circadian rhythms impact metabolism and the therapeutic effects of drugs. The purpose of this study was to determine the association between PER and CRY polymorphisms and caffeine citrate treatment response in infants with apnea of prematurity.Methods A total of 221 preterm infants of gestational age <34 weeks were included in this study (160 in the response group and 61 in the non-response group). The propensity score matching method was used to perform a 1:1 matching for all premature infants, and the general characteristics and clinical outcomes of the two groups were compared. The association between polymorphisms of the circadian transcription repressors PER and CRY and caffeine citrate treatment response in infants with apnea of prematurity was analyzed with co-dominant, dominant, recessive, and over-dominant models, as well as analysis of alleles. Generalized multifactor dimensionality reduction (GMDR) analysis was used to analyze the interaction between the PER and CRY genes.After propensity score matching, 45 preterm infants were included in each of the response and non-response groups, and there were no statistically significant differences in general characteristics between the two groups (P> 0.05). Infants in the non-response groups had a higher incidence of moderate and severe bronchopulmonary dysplasia (BPD) (P=0.043), retinopathy of prematurity (ROP) (P=0.035), and invasive ventilation (P=0.027), and their duration of oxygen use (P=0.041) was longer. When corrected for false discovery rate, the PER3 rs228669 recessive model (PFDR = 0.045) and the over-dominant model (PFDR = 0.045) were both associated with caffeine citrate treatment response. Preterm infants with the rs228669 CC genotype had a significantly lower rate of caffeine citrate non-response in the recessive model (OR=0.28,95% CI 0.12-0.66), which was significantly higher in preterm infants with the CT genotype in the over-dominant model (OR=4.18,95% CI 1.64-10.66). GMDR analysis revealed an interaction between the PER and CRY genes (P< 0.05).Conclusions Circadian rhythms may play a role in the response of premature infants to caffeine citrate, and polymorphisms of the PER and CRY genes may influence the effectiveness of caffeine citrate treatment for apnea of prematurity.